(untitled) (Jurnal Elektronika dan Telekomunikasi, 2021)
Automatic dependent surveillance-broadcast (ADS-B) is an equipment of a radar system to reach difficult areas. For radar applications, an ADS-B requires a low noise amplifier (LNA) with high gain, stability, and a low noise figure. In this research, to produce an LNA with good performance, an LNA was designed using a BJT transistor 2SC5006 with DC bias, VCE = 3 V, and current Ic = 10 mA, also a DC supply with VCC = 12 V, to achieve a high gain with a low noise figure. The initial LNA impedance circuit was simulated using 2 elements and then converted into 3 elements to obtain parameters according to the target specification through the tuning process, impedance matching circuit was used to reduce return loss and voltage standing wave ratio (VSWR) values. The LNA sequence obtains the working frequency of 1090 MHz, return loss of -52.103 dB, a gain of 10.382, VSWR of 1.005, a noise figure of 0.552, stability factor of 0.997, and bandwidth of 83 MHz. From the simulation results, the LNA has been successfully designed according to the ADS-B receiver specifications.